2012
DOI: 10.1128/jvi.00531-12
|View full text |Cite
|
Sign up to set email alerts
|

Elite Controllers with Low to Absent Effector CD8 + T Cell Responses Maintain Highly Functional, Broadly Directed Central Memory Responses

Abstract: Analyses of the breadth and specificity of virus-specific CD8؉ T cell responses associated with control of HIV have largely relied on measurement of cytokine secretion by effector T cells. These have resulted in the identification of HIV elite controllers with low or absent responses in which non-T-cell mechanisms of control have been suggested. However, successful control of HIV infection may be associated with central memory T cells, which have not been consistently examined in these individuals. Gagspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 50 publications
(71 reference statements)
6
85
2
3
Order By: Relevance
“…Eight out of nine of the ESs studied here have the protective HLA B*27 and/or B*57 class I alleles (Table 1). In contrast, some ESs in other larger cohorts do not have these protective alleles or strong HIV-specific CD8 ϩ T cell responses (8,49,51,65). It would be interesting to determine whether suppressive CD4 ϩ responses play a role in the control of viral replication in these patients.…”
Section: A) C)mentioning
confidence: 99%
“…Eight out of nine of the ESs studied here have the protective HLA B*27 and/or B*57 class I alleles (Table 1). In contrast, some ESs in other larger cohorts do not have these protective alleles or strong HIV-specific CD8 ϩ T cell responses (8,49,51,65). It would be interesting to determine whether suppressive CD4 ϩ responses play a role in the control of viral replication in these patients.…”
Section: A) C)mentioning
confidence: 99%
“…An ex vivo viral inhibition assay was carried out to determine the ability of CD8 ϩ T cells to suppress virus replication by measuring the amount of HIV p24 antigen as previously described (36,37). Log inhibition values were calculated by subtracting log 10 p24 values of the infected CD4 ϩ T cells cocultured with CD8 ϩ T cells from log 10 p24 values of the infected CD4 ϩ T cells without CD8 ϩ T cells at day 7.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular cytokine staining was performed as described previously (35,36). The cells were then acquired on a flow cytometer (LSR II; BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…In WR, it is possible that highly reactive HIV-specific memory CD8 ϩ T cells expand and acquire effector functions in response to relapses in viral replication, thereby controlling the virus when necessary. In fact, a recent report showed that CD8 ϩ T cells from WR HIC can gain the capacity to suppress HIV replication after a short period of in vitro stimulation with HIV peptides (18). However, cells from antiretroviraltreated patients have also been shown to acquire similar properties following peptide stimulation (19) but cannot prevent viral rebound following treatment interruption.…”
mentioning
confidence: 99%